Sport events tourism: A perspective analysis for the tourism sector - Palrão, T.; Filipe, J. (Modeling and new trends in tourism: A contribution to social and economic development, 2017)
Portugal has gradually emerged as a country holding excellent natural conditions for Tourism. It has a vast coastline extension, an extremely diversified landscape and has very interesting conditions to carry out a considerable number of different sporting activities, many of them being possible to be held all year round. Given the fact that there are not so many publications available in this area and taking into account a careful literature review on tourism, tourism sports events and on participants’ motivation, this chapter intends to define a set of necessary criteria used to study this subject in order to understand the ways and possible strategies for this sector development. This study aims to contribute for the success of this type of tourism. It is also necessary to make an incursion on the tourist’s profile to understand the main variables and characteristics in this type of events. The main goal of this study is to conceptualize the primary features tourists give major relevance to in this area. Based on these findings, the fundamental factors of why this type of events are consistent will successfully be understood and worked conducting this study to be a contribution for the sustainable growth of the industry’s revenue. This approach will be applied to the Portuguese context in this area.